The worldwide population genetics of Harmonia axyridis: how the invasive Harlequin Ladybird invaded, and moves within, South Africa - Collop, Amy (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.